British Colonialism and Women Empowerment in India - Bharti Nandwani; Punarjit Roychowdhury (Global Labor Organization (GLO), 2023)
This paper examines the long-term link between British colonialism and women empowerment in India. We compare women's contemporary economic outcomes across areas that were under direct British colonial rule with areas that were under indirect colonial rule. Controlling for selective annexation using a specific policy, we find that women who live in areas that were under direct British rule, compared to their counterparts, are better off in terms of almost all measures of women empowerment including employment, within-household decision-making, mobility, etc. We also document positive impacts of British colonialism on several drivers of women empowerment including education, fertility, marital age, gender norms, etc. While our study of the underlying transmission channels is challenged by data limitations, we argue that legal and institutional changes brought in by the British in favor of women and the West-inspired social reformation movement of the 19th century may be relevant to explaining this long-term link.
Keywords: J12; J16; N35; O12; 330; Colonialism; Gender Inequality; India; Intimate Partner Violence; Women Empowerment